The Analysis of Code Switching In English Conversation By The Second Grade Students at The SMP Negeri 2 Kefamenanu - Ulu, Paskalia Domina ((JELE) Journal Of English Language and Education, 2020)
Ulu, Paskalia Domina. 2020. The Analysis of the Code Switching in English Conversation  of by the Second Grade Students of  SMP NEGERI 2 KEFAMENANU in the school Year of 2019/2020. Timor University. Main advisor (1). Imanuel Kamlasi, S. Pd., M. Pd. Associate advisor (2). Drs. Edmundus Bouk,  M. Pd.The goals of this study are to find out the code switching that are used by the students in conversation and to know the code switching used by the students in the conversation. This study used qualitative method and the writer did a case study of this research. The subject of this study are 20 students in 10 groups. The instrument of this research is the transcripts’ of the students’ conversation. The result of the study showed that the students’ made Code Switching  in conversation because they lack of vocabulary, rare to speak English and shy to express their feeling or idea. The highest percentage is situational code switching which total percentage 33. 33%. Then, followed tag code switching which total percentage 25%. Then, followed by inter-sentential and intra sentential code switching which total percentage 16, 7%. Then, the lowest percentage is metaphorical code switching which total percentange 8. 33%.